Digital transformation of mortality reporting using an ICD-11 integrated death certificate system in Suriname - Jerry Toelsie; Richard Mendes; Ritesh Dhanpat; Radjesh Ori; Rosmond Adams; Coen van Gool; Carine Alsokhn; Katri Kontio; and Yafflo Ouattara (Revista Panamericana de Salud Pública)
The Ministry of Health of Suriname has replaced the outdated 1958 paper-based death certificate with an adapted digital version based on the World Health Organization international form of Medical Certificate of Cause of Death, integrated with the International Classification of Diseases 11th Revision (ICD-11) coding tool. This digital system, which comprises a mobile application and a web-based platform, enables direct selection of diagnoses using the ICD-11 codes, including post-coordination (code combinations) and the use of extension codes. Acting as a centralized hub, it allows the Ministry of Health to efficiently extract and analyze mortality data. Training programs have been provided for all medical doctors to ensure effective adoption. This initiative aligns with the Pan American Health Organization’s Information Systems for Health 2024–2030 strategy, which emphasizes digital transformation to strengthen health systems in the Americas. It also reflects Suriname’s commitment to the 2019 World Health Assembly resolution to adopt ICD-11 as the global standard for cause-of-death reporting. By improving data quality, flow, and accessibility, the system supports timely reporting and reduces workload. Furthermore, it addresses a critical gap, as limited published research exists on the implementation of electronic Medical Certificate of Cause of Death (eMCCD) in the Americas. The system will undergo evaluation after one year to assess its impact and guide further improvements.